Hubungan Komunikasi Terapeutik Bidan dengan Kecemasan Ibu Bersalin di RS Prasetya Bunda Tasikmalaya Tahun 2023 - Elis Muharomah; Wintarsih Wintarsih (Malahayati Nursing Journal, 2024)
ABSTRACT The maternal mortality rate in West Java in 2017 based on the 2017 health profile was 76.03 per 100,000 KH, when compared to the proportion of MMR in 2017 that was targeted, the MMR of West Java Province was already below the 2015 national target (MGDS). According to the City Health Office Tasikmalaya in 2019 the maternal mortality rate was 1 case. One of the factors that influence the safety of delivery is the factor of anxiety during the delivery process. In the delivery process, therapeutic communication will provide comfort during childbirth. The results of the initial survey in the Delivery Room of Prasetya Bunda Hospital, through observations of 5 mothers giving birth in the 1st stage, four mothers experiencing anxiety. To analyze the relationship between midwives' therapeutic communication and the anxiety of mothers giving birth at Prasetya Bunda Tasikmalaya Hospital in 2023. This type of research is an analytic descriptive study using a cross sectional approach. The research location will be carried out at Prasetya Bunda Tasikmalaya Hospital. The time of the research will be carried out from March to June 2023. The population in this study are mothers who give birth at Prasetya Bunda Tasikmalaya Hospital with an average number of 30 people per month. The sampling technique in this study used total sampling so that the sample was 30 people. The first measuring tool is about therapeutic communication as many as 15 question items, while the second measuring tool uses the Hamilton Rating Scale for Anxiety (HRSA) questionnaire. Data were analyzed using univariate analysis of frequency distribution and bivariate chi square analysis. The results of the Chi-Square statistical test at a significant level of 95% with α = 0.05 show that the P-value (0.002) α = 0.05. It can be concluded that Ho is rejected. Thus it can be interpreted that there is a relationship between midwives' therapeutic communication with the anxiety of mothers giving birth at Prasetya Bunda Tasikmalaya Hospital in 2023 Keywords: Therapeutic Communication, Midwives, Anxiety, Maternity Mothers.  ABSTRAK Angka kematian ibu di Jawa Barat pada tahun 2017 berdasarkan profil kesehatan 2017 sebanyak 76,03 per 100.000 KH, jika dibandingkan dengan proporsi AKI tahun 2017 yang ditargetkan maka AKI Provinsi Jawa Barat sudah berada dibawah target nasional (MGDS) tahun 2015. Menurut Dinas kesehatan Kota Tasikmalaya pada tahun 2019 Angka Kematian Ibu sebanyak 1 kasus. Salah satu faktor yang berpengaruh terhadaap keselamatan persalinan adalah faktor kecemasan pada saat proses persalinan. Pada proses persalinan komunikasi terapeutik akan memberikan kenyamanan saat bersalin. Hasil survey awal di Ruang Persalinan RS Prasetya Bunda, melalui pengamatan terhadap 5 orang ibu bersalin kala 1, empat ibu bersalin mengalami kecemasan. Untuk menganalisis hubungan komunikasi terapeutik bidan dengan kecemasan ibu bersalin di RS Prasetya Bunda Tasikmalaya tahun 2023. Jenis penelitian ini merupakan penelitian deskriptif analitik menggunakan pendekatan cross sectional. Lokasi penelitian akan dilaksanakan di RS Prasetya Bunda Tasikmalaya. Waktu penelitian akan dilaksanakan mulai bulan Maret s/d Juni 2023. Populasi pada penelitian ini adalah ibu yang melahirkan di RS Prasetya Bunda Tasikmalaya dengan jumlah rata-rata per bulan sebanyak 30 orang. Teknik pengambilan sampel pada penelitian ini menggunakan total sampling sehingga sampel berjumlolah 30 orang. Alat ukur pertama tentang komunikasi terapeutik sebanyak 15 item pertanyaan, sedangkan alat ukur kedua menggunakan kuesioner Hamilton Rating Scale for Anxiety (HRSA). Data dianalisis menggunakan analisis univariat distribusi frekuensi dan analisis bivariat chi square. Hasil output uji statistik Chi-Square yang pada tingkat signifikan 95% dengan α= 0,05 diketahui bahwa nilai P-value (0,002) α= 0,05. Dapat disimpulkan bahwa Ho ditolak. Dengan demikian dapat diartikan bahwa ada hubungan komunikasi terapeutik bidan dengan kecemasan ibu bersalin di RS prasetya bunda tasikmalaya tahun 2023. Kata kunci: Komunikasi Terapeutik, Bidan, Kecemasan, Ibu Bersalin.